2016
DOI: 10.5152/tjar.2016.52385
|View full text |Cite
|
Sign up to set email alerts
|

Management of Neuraxial Anaesthesia for Emergent Caesarean Section for Placenta Previa

Abstract: Plasenta akreta, inkreta veya perkrata gibi plasenta yapışma anomalileri ciddi postpartum kanama riski nedeniyle morbidite ve mortalite artışına neden olabilirler. Otuz altı haftalık multipar gebede plasenta previaya bağlı vajinal kanama nedeniyle acil sezaryen için uygulanan spinal anestezi yönetimi ve cerrahi yaklaşımı literatür eşliğinde tartışarak sunmayı amaçladık. Spinal anestezi için intratekal olarak 12 mg hiperbarik bupivakain+10 µg fentanil+ 150 µg morfin verildi. Göbek kordonu klemplendikten sonra o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In addition, bleeding and increased surgical manipulation prolong the operating time, and these are other factors causing discomfort in an awake patient [13,18,19]. Nevertheless, in a questionnaire applied to obstetric anesthetists, it was reported that 65% applied SA to PP cases where complications are not expected, and GA was preferred by 69.2% in cases with suspected PA and by 96.2% in cases diagnosed with PA. Gunaydın et al have reported successful management with SA in patients with PP and PA [20]. In the current study, SA was applied to PP cases where fewer complications were expected and GA was preferred for the other PP cases and all but one of the PA cases.…”
Section: Discussionmentioning
confidence: 75%
“…In addition, bleeding and increased surgical manipulation prolong the operating time, and these are other factors causing discomfort in an awake patient [13,18,19]. Nevertheless, in a questionnaire applied to obstetric anesthetists, it was reported that 65% applied SA to PP cases where complications are not expected, and GA was preferred by 69.2% in cases with suspected PA and by 96.2% in cases diagnosed with PA. Gunaydın et al have reported successful management with SA in patients with PP and PA [20]. In the current study, SA was applied to PP cases where fewer complications were expected and GA was preferred for the other PP cases and all but one of the PA cases.…”
Section: Discussionmentioning
confidence: 75%